Long-term follow-up of retinoblastoma survivors: Experience from India - Seth, Rachna; Singh, Amitabh; Guru, Vijay; Chawla, Bhavna; Pathy, Sushmita; Sapra, Savita (South Asian Journal of Cancer, 2017)
Background: Retinoblastoma (Rb) is the most common primary intraocular tumor of infancy and childhood. Survivors' ocular and visual problems and increased risk for subsequent malignancy are well documented, but data on long-term health status of Rb survivors are limited, this being particularly true for India. Methodology: Children who had completed treatment for Rb at least 2 years ago before and were under follow-up at the after cancer treatment clinic were evaluated. Results: In our series of 213 patients, the median age was 29 months, there was a male preponderance, and majority had unilateral disease. Enucleation was done in almost three-fourth and 3% underwent bilateral enucleation. Majority of the patients received chemotherapy, and few received radiation. Growth was affected in about one-third and majority were those who had received radiation. Diminished vision was noticed in about one-sixth. Orbital hypoplasia and contracted socket were seen in 14.1% cases. 2.7% were hearing impaired. About one-sixth had a global intelligence delay. Second neoplasms were seen in 0.01%. No other abnormalities were seen. Conclusions: Common late effects in our Rb survivors include diminished vision in the salvage eye, intellectual disability, and contracted socket; there is a need for timely institution of prosthesis to avoid late effects such as hypoplasia, contracted sockets, and better cosmesis and enhanced self-esteem. Second neoplasm is a concern. Lifelong follow-up and counseling of a healthy lifestyle are needed for Rb survivors.
Keywords: Children; long-term follow-up; retinoblastoma